ANALISIS KINERJA APLIKASI INVENTARIS BERBASIS WEB - Dodi Nofri Yoliadi (JSR : Jaringan Sistem Informasi Robotik, 2023)
Inventory Application is a web-based application developed to solve problems in inventory data processing. Payakumbuh College of Technology is a higher education institution in the city of Payakumbuh. Payakumbuh College of Technology is experiencing problems managing inventory data, which is still classified as manual. Therefore, a web-based inventory application was built at the Payakumbuh College of Technology, which was made using PHP, MySQL, and the CodeIgniter framework. To find out how good the quality of the application is, it is necessary to evaluate the performance of the application. GTMe-trix will be used as software testing to evaluate the performance of this application. User responses are also used as a reference for application developers in analyzing the usability of applications that have been built. The overall results of testing the performance efficiency of the inventory application show grade A results and page load times of 5.59 seconds. Therefore, the performance of this application can be stated to be very good and feasible to use. Overall, the informant's level of satisfaction with the use of this inventory application was stated at the satisfied stage. The indicators that still need improvement are barcode labels and barcode scanning automatically.